Stroboscopic detection of nuclear resonance in an arbitrary scattering channel. (3rd February 2015) - Deák, L.; Bottyán, L.; Callens, R.; Coussement, R.; Major, M.; Nasu, S.; Serdons, I.; Spiering, H.; Yoda, Y.
<x xml:space="preserve">Abstract</x> The theory of heterodyne/stroboscopic detection of nuclear resonance scattering is developed, starting from the total scattering matrix as a product of the matrix of the reference sample and the sample under study. This general approach holds for all dynamical scattering channels. In the forward channel, which has been discussed in detail in the literature, the electronic scattering manifests itself only in an energy‐independent diminution of the scattered intensity. In all other channels, complex resonance line shapes of the heterodyne/stroboscopic spectra are encountered, as a result of the interference of electronic and nuclear scattering. The grazing‐incidence case will be evaluated and described in detail. Experimental data of classical X‐ray reflectivity and their stroboscopically detected resonant counterpart spectra on the [natFe/57Fe]10 isotope periodic multilayer and antiferromagnetic [57Fe/Cr]20 superlattice are fitted simultaneously.